Mobile technology for street trading in Tanzania: A design science research approach for determining user requirements. Issue 5 (4th April 2021) - Rumanyika, Joel; Apiola, Mikko; Mramba, Nasibu Rajabu; Oyelere, Solomon Sunday; Tedre, Matti
Abstract: Street trading is an economic activity that is conducted by street traders in numerous urban parts of Tanzania. Street traders use mobile technology to search for markets. This study mapped the wants and needs of Tanzanian street traders and their customers in order to better understand the potential and pitfalls of technology to help their trade activities. Qualitative data were collected using in‐depth interviews with 22 street traders and 22 customers. In addition, two focus group discussions with 20 participants, including street traders and customers, were conducted. Data were analyzed through content analysis. The results identified a number of technology wants and needs shared by traders and customers that would ease the customers' access to products they want, and support the traders to promote their products, locate where the users are, support business growth, and predict sales potential. This research study contributes to understanding the technology needs of one marginalized group in Tanzania. The study facilitates discussion on the suitability of design research in the context of informal worker communities, and it points toward a path for design research of information systems that are grounded on the needs and knowledge of end‐users in their communities and contexts of use.